2017
DOI: 10.3899/jrheum.160693
|View full text |Cite
|
Sign up to set email alerts
|

Disease Characteristics and Rheumatoid Arthritis Development in Patients with Early Undifferentiated Arthritis: A 2-year Followup Study

Abstract: Only 9.8% of patients with UA fulfilled the 2010 RA criteria during 2-year followup. Small joint involvement and swollen shoulder joint were among the factors associated with RA development. In two-thirds of patients with UA, the arthritis resolved without use of DMARD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Sir, Multiple studies have demonstrated that shoulder complaints are frequent in RA [ 1 , 2 ]. Recently, it has been shown that shoulder involvement is predictive of RA development in patients with undifferentiated arthritis and its value is comparable with that of small joint involvement [ 3 ]. The phase of clinically suspect arthralgia precedes the phase of clinically apparent arthritis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sir, Multiple studies have demonstrated that shoulder complaints are frequent in RA [ 1 , 2 ]. Recently, it has been shown that shoulder involvement is predictive of RA development in patients with undifferentiated arthritis and its value is comparable with that of small joint involvement [ 3 ]. The phase of clinically suspect arthralgia precedes the phase of clinically apparent arthritis.…”
mentioning
confidence: 99%
“…In this study, US of both shoulders was made at baseline. US abnormalities of the biceps tendon [ 1 ], the glenohumeral joint [ 2 ] and the subdeltoid bursa [ 3 ] were assessed for tenosynovitis, arthritis and bursitis. Thereafter, patients were followed for the course of 1 year (with 6-monthly visits) for the development of clinically apparent IA, which was verified by the treating physician.…”
mentioning
confidence: 99%
“…A 55-year-old, right-handed man developed oligoarthritis affecting his ankles. Two months later, a rheumatologist's evaluation did not identify features of RA or another inflammatory disorder, and the patient was subsequently diagnosed with an undifferentiated arthritis 3 (table 1). Four months later, he developed overnight (within 6 hours) explosive onset of burning feet pain.…”
Section: Case Reportmentioning
confidence: 99%
“…Small fiber neuropathy presenting during the antecedent period of undifferentiated arthritis prior to rheumatoid arthritis Julius Birnbaum, MD, MHS I n contrast to Sjögren syndrome (SS), 1 small fiber neuropathies (SFN) associated with rheumatoid arthritis (RA) have been sparsely reported. 2 Furthermore, many patients with RA pass through an antecedent period termed undifferentiated arthritis (UA), 3 in which they may experience an inflammatory arthritis not satisfying criteria for RA or another inflammatory syndrome. SFN may be a rare complication occurring during this presaging period of UA.…”
mentioning
confidence: 99%
“…In the 2010 American College of Rheumatology/European League Against rheumatism (ACR/EULAR) classification criteria, 6 rheumatoid factor (RF) and anticitrullinated protein antibodies (ACPA) were recommended as a good marker for the diagnosis of RA. However, a percentage of patients with undifferentiated arthritis faces big challenges that arise from conventional diagnosis and classification criterion 7 and RF is not very specific for RA and may also be detected in patients with other rheumatic disorders or infections, or in apparently healthy individuals 8 . Therefore, it is necessary to incorporate some novel RA indicators into the diagnostic criteria of RA.…”
Section: Introductionmentioning
confidence: 99%